2008
DOI: 10.1111/j.1445-5994.2008.01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing antifungal drug dosing and monitoring to avoid toxicity and improve outcomes in patients with haematological disorders

Abstract: Antifungal prophylaxis, empirical therapy and treatment of established fungal infections in the haematology population may be associated with significant toxicity or drug interactions leading to sub-therapeutic antifungal drug concentrations and poorer clinical outcomes. These risks may be minimised by clinical assessment, laboratory monitoring of biochemical or haematological indices, avoidance of particular drug combinations and dose modification in certain circumstances. Specific measures, such as the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 143 publications
0
32
0
4
Order By: Relevance
“…However, it has been reported that side effects are higher when compared to other triazoles (17,18). TDM of posaconazole has been recommended when drug-drug interactions are suspected (2), and a clinical trial showed that higher posaconazole concentrations were associated with a higher number of responders to treatment of aspergillosis (14). Moreover, posaconazole metabolism shows pronounced individual variability of 38%-82% in cohorts of severely ill patients (1,5,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that side effects are higher when compared to other triazoles (17,18). TDM of posaconazole has been recommended when drug-drug interactions are suspected (2), and a clinical trial showed that higher posaconazole concentrations were associated with a higher number of responders to treatment of aspergillosis (14). Moreover, posaconazole metabolism shows pronounced individual variability of 38%-82% in cohorts of severely ill patients (1,5,19).…”
Section: Introductionmentioning
confidence: 99%
“…Triazoles affect ergosterol biosynthesis of yeasts and fungi by specific inhibition of 14a-demethylase (CYP51). Indications for therapeutic drug monitoring (TDM) comprise non-linear pharmacokinetics, high intra-individual metabolic variability, narrow therapeutic range, unexpected toxicity, and possible drug interactions (1)(2)(3). For triazole antifungals with an approval date before 2005, TDM methods have been developed for itraconazole and its main active metabolite, hydroxyitraconazole (4-7), as well as for voriconazole (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Due to specific metabolic pathways of triazoles, drug interactions in selected patients, such as AML patients, may often cause sub-therapeutic concentrations. In particular, VRC is a substrate and inhibitor of CYP2C19, CYP2C8/9 and CYP3A4 [1,2] and PSC is an inhibitor of CYP3A4, metabolized by glucuronidation 4 . Due to the metabolic bind especially at CYP3A4 site between azoles and current therapy for AML treatment, and to therapeutic window (1-5,5 µg/mL) reported for VRC [8], and thresholds of efficacy reported for PSC (0.7 µg/mL for prophylaxis and 1.25 mg/mL for treatment) 11,12 , antifungal TDM is gaining increasingly importance for selected populations such as AML patients.…”
Section: Resultsmentioning
confidence: 99%
“…Antifungal agents of the azole class are metabolized by the cytochrome P450 (CYP450) system, such as voriconazole (VRC, Figure 1), a widely used broad-spectrum triazole substrate of CYP2C19, CYP3A4 and CYP2C9 isoforms [2]. Posaconazole (PSC, Figure 2), instead, likewise broad-spectrum triazole, is also substrate of CYP3A4 but primarly undergoes glucuronidation [3,4], leading to a potential for drug-drug interactions minor than that for VRC [1]. Then, co-administration of drugs that induce CYP450 metabolism can result in undetectable circulating levels of VRC and PSC, while coadministration of CYP450 inhibitors may cause an increase of these levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation